SURVEI JUMLAH TOTAL KUMAN DAN KEBERADAAN Vibrio cholerae PADA PETIS YANG DIJUAL PEDAGANG TAHU PETIS DI KECAMATAN TEMBALANG KOTA SEMARANG - Fitriyana, Meuthika Noor; Hestiningsih, Retno; Sutiningsih, Dwi (Jurnal Kesehatan Masyarakat (Undip), 2015)
Petis is a food that is seems like porridge,sticky and elastic , dark brown or black coloured which is  made from fish,shrimp,kupang or meat. As a traditional food, petis may pose microbiological hazard. Vibrio cholerae is one of bacteria that can be found on petis. The aim of this research was to describe total plate count and the presence of Vibrio cholerae in petis sold by tahu petis sellersin Tembalang The District of Tembalang Semarang. This research is a descriptive used cross sectional. Total plate count examination used pour plate methods. WhileVibrio cholerae examination uses TCBS media and biochemical test used TSIA, indole, and cimmon’s citrat.  The sample in this research were petis sold by tahu petis sellersin The District ofTembalang Semarang amounted to 25 sellers.The result showed that all of sample (100%) were not eligible based of SNI quality requirement and 3 sample (12%) contained Vibrio cholerae. The result of interview and observation showed that most of the sellershas done selection of petis (64%) and petis storage (56%), in the other hand at the processing (52%), presentation (76%), and place sanitation process (56%) most of the sellers in bad category. Petis vendor should pay more attention to food handling , local health agencies should provide guidance about food handling and also to other researcher should give more attention to the possibilty of other bacteria.